DIGITAL BRANDING STRATEGY MSMES FOR SNACKS IN TANJUNG MULIA VILLAGE - Nurbaiti; Mandalika, Jeane Agretta; Dinata, Dian Novita; Lubis, Ikhwan Rinaldi; Ardiansyah, Fitra (Yayasan Amanah Nur Aman, 2025)
Digital transformation provides significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to strengthen their brand identity and expand market reach. This study analyzes the impact of digital transformation on brand identity development of unbranded MSMEs in Tanjung Mulia Village, Langkat Regency. Using a qualitative case study method through interviews, observations, documentation, and focus group discussions, the research focused on Handayani Crispy, a traditional snack business without an official brand. The findings show that digital interventions—such as creating a website, providing digital literacy training, and introducing a consistent brand identity—significantly enhanced product visibility, consumer trust, and the owner’s self-confidence. Consumers responded positively to the branded products, viewing them as more professional and suitable as gifts. However, challenges remain, including limited digital literacy, unstable internet infrastructure, and the owner’s time constraints. This study highlights the importance of integrating digital technology with branding strategies to empower MSMEs in rural areas. Recommendations include continuous digital literacy training, packaging innovation, product diversification, social media utilization, and collaboration with local stakeholders to ensure sustainable digital transformation.